Work ethics and social concerns: a study on teacher’s performance - Firdausiyyah, Kunti Zakiyyatal; Latipun; Siti Suminarti Fasikhah (Universitas Muhammadiyah Malang, 2024)
One of the goals of working is to get salary. But there are some individuals who work for specific goals. One of them is teacher in Islamic boarding schools which requires a lot of extra contribution because they are required to be active in Islamic boarding school activities. This research aims to reveal in depth and provide an overview of the work ethic and social concerns adhered by teachers in Islamic boarding schools by looking at how they perform on a daily basis. This research uses a qualitative method with phenomenological approach. This research was conducted by interviewing 4 subjects with predetermined criteria. Subject selection was carried out using accidental sampling technique. Data collection was carried out using semi-structured interviews. The results of this research are work ethic shown by the teacher’s seriousness and responsibility in overcoming problems that occur, and maximizing their performance while teaching. Coupled with the cooperation built with fellow colleagues, sincerity in carrying out tasks, and independence in solving problems experienced at work. The work ethic of teachers in Islamic boarding schools is colored by social care values which improve their performance. The value of social concerns originates from behavior and norms as well as values adapted from Islamic values commonly adhered by Islamic boarding schools.